Contemporary Da'wah and Response to the Ecological Crisis: Integrating Islamic Values and Environmental Awareness - Aridah, Kasrunil; Dahri, Harapandi; Hakiki, Baenul (TASAMUH, 2025)
This paper examines the role of contemporary da'wah in responding to the ecological crisis that has become a global challenge in the 21st Century. By referring to Islamic values that view humans as khalifah on earth, this research highlights the importance of integrating Islamic theological principles with ecological awareness to foster a robust environmental conservation ethic. The da'wah approach developed is directed to be relevant and contextual to the socio-cultural conditions of Muslims today so that the message of environmental sustainability does not only become an abstract idea but is implemented in the form of commitment and real action. Through literature studies and content analysis of various da'wah materials that address environmental themes, this study found that da'wah strategies that combine religious values and ecological awareness can collectively foster moral orientation and environmentally friendly behavior. The research recommends the development of innovative and collaborative da'wah methods that utilize digital media and social networks to expand the reach and impact of the Islam-based environmental conservation movement.